1975
DOI: 10.1159/000225017
|View full text |Cite
|
Sign up to set email alerts
|

Thymus-Dependent Lymphocyte Function in Dimethylnitrosamine-Induced Renal Carcinogenesis is Not Depressed

Abstract: As one measure of cell-mediated immunity, the blastogenic response of enriched spleen lymphocytes to phytohaemagglutinin (PHA) was assayed at sequential daily and weekly intervals following the administration of dimethylnitrosamine (DMN) as a single dose sufficient to induce renal tumours in 100% of surviving rats. PHA responsiveness of DMN-treated rats was not suppressed at any stage of tumour induction in contrast to rats which had been intentionally immunodepressed by neonatal thymectomy. It was concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The immunodepressive action exerted by DMN on anti-SRBC antibody production stands in marked contrast to the total lack of effect on one function of T lymphocyte-mediated cellular immunity, namely, the blastogenic response to phytohemagglutinin as ob served in an earlier study [14]. The cell populations comprising the immunoregulatory network include dis crete subsets of lymphocytes with specific functions that interact to maintain homeostasis [32], Although blas togenic sensitivity to phytohemagglutinin cannot be assigned to any specific subset of T lymphocytes in the rat as yet, the combined results of these two studies indicate that DMN.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The immunodepressive action exerted by DMN on anti-SRBC antibody production stands in marked contrast to the total lack of effect on one function of T lymphocyte-mediated cellular immunity, namely, the blastogenic response to phytohemagglutinin as ob served in an earlier study [14]. The cell populations comprising the immunoregulatory network include dis crete subsets of lymphocytes with specific functions that interact to maintain homeostasis [32], Although blas togenic sensitivity to phytohemagglutinin cannot be assigned to any specific subset of T lymphocytes in the rat as yet, the combined results of these two studies indicate that DMN.…”
Section: Discussionmentioning
confidence: 69%
“…The effect of the carcinogenic dose of DMN on cellmediated immune function in this system has been de termined earlier by assaying the blastogenic response of rat spleen lymphocytes to phytohemagglutinin [14], As an extension of that study, the effect of DMN on antibody production in the rat is now reported, using an antigen which is completely thymus-independent (B cell) and one which requires T and B cell coopera tion. As in the earlier investigation, the immunological effects were assessed during the total sequence of in vivo events, from the acute phase immediately follow ing the carcinogenic insult, up to the presence of ma croscopic, debilitating neoplasms in the kidney.…”
Section: Introductionmentioning
confidence: 91%